SUCCESSFUL NON-OPERATIVE TREATMENT IN MICROCYSTIC LYMPHATIC MALFORMATION OF THE TONGUE: A CASE REPORT - Nuri Fitriasari; Irna Sufiawati (ODONTO : Dental Journal, 2022)
Background: Microcystic lymphatic malformation (MLM) is an abnormal congenital growth of lymphatic vessels. It may occur in any part of the human body, with 75 % cases found in the head and neck, including in oral cavity. This case report aimed to describe a case of MLM in a child who was successfully treated non-operatively with antibiotics and corticosteroid.Case Report: A 4-year-old child came to Oral Medicine Clinic of Dr. Hasan Sadikin General Hospital, Bandung, with a chief complaint lesions of the tongue since a year ago, accompanied by bleeding in the affected areas but not pain. Patient gave history of recurrent episodes of the symptoms since 7 months old. Result : Ultrasonography was performed and diagnosis of microcystic lymphatic malformation was established. Systemic oral corticosteroid, antibiotics, and multivitamins were given and the lesions showed significant improvement after 2-weeks treatment. Conclusion: Therapy of MLM with antibiotics and systemic oral corticosteroid significantly improved patient’s condition, and ultrasonography may be used as a diagnostic modality in MLM diagnosis.